2019
DOI: 10.3390/genes10060464
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Genomic and Clinical Data Reveals Intrinsic Characteristics of Bladder Urothelial Carcinoma Progression

Abstract: The progression of bladder cancer is generally a complex and dynamic process, involving a variety of biological factors. Here, we aimed to identify a set of survival-related genes that play an important role in the progression of bladder cancer and uncover their synergistic patterns. Based on the large-scale genomic profiling data and clinical information of 404 bladder cancer patients derived from The Cancer Genome Atlas (TCGA) database, we first discovered 1078 survival-related genes related to their surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It has been demonstrated that modulating gene expression is one of the most important ways for CNV to play diversi ed roles in diseases [11][12][13][14]. In this study, the results showed that 5022 gene expressions in TCGA were signi cantly modulated by CNV (p <0.05, adjusted p <0.2) and 577 genes in TARGET were signi cantly associated with CNV (p <0.05, adjusted p <0.2).…”
Section: Integrative Analysis Of Gene Expressions In Concordance Withmentioning
confidence: 59%
“…It has been demonstrated that modulating gene expression is one of the most important ways for CNV to play diversi ed roles in diseases [11][12][13][14]. In this study, the results showed that 5022 gene expressions in TCGA were signi cantly modulated by CNV (p <0.05, adjusted p <0.2) and 577 genes in TARGET were signi cantly associated with CNV (p <0.05, adjusted p <0.2).…”
Section: Integrative Analysis Of Gene Expressions In Concordance Withmentioning
confidence: 59%
“…From that, Benjamini and Hochberg's false discovery rate (FDR) may be a better choice. Likewise, many previous works [49][50][51][52][53] related the expression levels of each identified driver gene to prognostic value (e.g., the overall survival of patients), and the genes when P-value ≤ 0.05 (Log-rank test) were considered to define significant association. Again, FDR control is crucial, so we developed the tool 'geneSA' (https ://githu b.com/huyng uyen2 50896 /geneS A) to automatically do the above task and only preserve the genes if Q-value ≤ 0.05 (Benjamini-Hochberg FDR).…”
Section: List Of Improvements Proposed In the Work Selection Of Drivmentioning
confidence: 99%
“…1, Stage 2-Step 4) and patient stratification ( Fig. 1, Stage 2-Step 5), which is a common selection from previous studies 10,11,14,49,51,52 . Furthermore, these previous works performed the hierarchical clustering method using complete linkage and Euclidean distance for the clustering task in co-expression network construction and patient stratification.…”
Section: Selection Of Tools For Unsupervised Identification Of Co-expmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous miRNA studies have identified histological grade and stage (pT) classification-dependent miRNA expression and have proven the existence of miRNAs alterations related to the two divergent pathways found in the development of NMIBC and MIBC [8,9]. Only a few studies have analyzed miRNA as a prognostic and predictive biomarker [10,11,12]. Each miRNA can have multiple targets, and changes in their expression profile could have a magnified effect on cellular phenotype.…”
Section: Introductionmentioning
confidence: 99%